2019
DOI: 10.1088/1748-9326/ab1bc5
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting human influences and macro-environmental factors on fire activity inside and outside protected areas of North America

Abstract: Human activities threaten the effectiveness of protected areas (PAs) in achieving their conservation goals across the globe. In this study, we contrast the influence of human and macro-environmental factors driving fire activity inside and outside PAs. Using area burned between 1984 and 2014 for 11 ecoregions in Canada and the United States, we built and compared statistical models of fire likelihood using the MaxEnt software and a set of 11 key anthropogenic, climatic, and physical variables. Overall, the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…A poll (Harris Poll, 2020) suggested that nearly two in five urban residents in the United States considered moving to a less crowded place. Outmigration from cities into rural areas due to the COVID-19 pandemic could have multiple impacts on rural communities near forests by further stressing services (Mueller et al, 2021), as well as on forest management, specifically from exacerbating the impacts of expanding the wildland-urban interface (WUI) on wildland firefighting, wildlife conflicts, and changing expectations of forest management (Radeloff et al, 2005;Hammer et al, 2009;Abrams et al, 2014;Mansuy et al, 2019). A recent survey of the rural western states in the United States is an example of changing expectations; it showed weak support for logging (41%), as opposed to 81% who supported traditional farming and ranching (Farrell et al, 2020).…”
Section: How Society Respondedmentioning
confidence: 99%
“…A poll (Harris Poll, 2020) suggested that nearly two in five urban residents in the United States considered moving to a less crowded place. Outmigration from cities into rural areas due to the COVID-19 pandemic could have multiple impacts on rural communities near forests by further stressing services (Mueller et al, 2021), as well as on forest management, specifically from exacerbating the impacts of expanding the wildland-urban interface (WUI) on wildland firefighting, wildlife conflicts, and changing expectations of forest management (Radeloff et al, 2005;Hammer et al, 2009;Abrams et al, 2014;Mansuy et al, 2019). A recent survey of the rural western states in the United States is an example of changing expectations; it showed weak support for logging (41%), as opposed to 81% who supported traditional farming and ranching (Farrell et al, 2020).…”
Section: How Society Respondedmentioning
confidence: 99%
“…This upward shift is more complex than simple climate change, as fire frequency and intensity were also found to be significant drivers (Luckman & Kavanagh, ). In North America, shifts toward hotter, more frequent wildfires has been linked to climate change (Kirchmeier‐Young, Gillett, Zwiers, Cannon, & Anslow, ; Mansuy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that climate factors (high temperature, moderate precipitation, and dry spells) were the most important drivers at the global scale, although at the regional scale, the models exhibited higher variability due to the influence of anthropogenic factors. At a continental scale, Mansuy et al (2019) used MaxEnt to show that climate variables were the dominant controls (over landscape and human factors) on area burned for most ecoregions for both protected areas and outside these areas, although anthropogenic factors exerted a stronger influence in some regions such as the Tropical Wet Forests ecoregion. Masrur et al (2018) used RF to investigate controls on circumpolar Arctic fire and found that June surface temperature anomalies were the most important variable for determining the likelihood of wildfire occurrence on an annual scale.…”
Section: Landscape Controls On Firementioning
confidence: 99%